Monetary Practices of Traditional Rural Communities in Ethiopia: Implications for New Financial Technology Design. (1st November 2016) - Woldmariam, Mesfin F.; Ghinea, Gheorghita; Atnafu, Solomon; Groenli, Tor-Morten
Abstract : With the development of ubiquitous technologies that support the digitization of money, research is needed on how individuals' private life practices are affected by new technological financial systems and how cash-based practices can inform their design. In this article, we report the cash-based monetary practices of one Ethiopian rural community and identify their implications for the design of new financial technology. Particularly, we focus on addressing the question, What characteristic features should go into the design of mobile money application(s) to embody a rural Ethiopian community's money practices in social (marriage and death) and religious contexts? Primary data on everyday practices of the community were collected. Analysis of our data reveals that new financial technology design should support lived experiences such as embedded social meaning, segregated and aggregate money control, restricted money use, identity extension and hiding, refusal and acceptance of donations, disclosed and secret money practices, and assigning aesthetics to money. The article concludes by discussing possible ways of mapping these concepts into financial system design, thus contributing toward the development of cashless transactions and a cashless society.